Physiological stress responses and meat quality of rabbits subjected to different road transportation and slaughter methods - Khadijah, Nakyinsige (2014)
This study describes the link between physiological stress responses to transport and slaughter to meat quality using rabbit as a model. The first experiment aimed at determining physiological stress responses and meat quality of rabbits subjected to different transport durations. A control group of ten rabbits remained at the farm and was not transported (T1) while the other two groups of 40 bucks each were transported for either 1 h (T2) or 3 h (T3). Transportation caused a significant rise in aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatine kinase (CK) activities, packed cell volume, haematocrit, plasma protein, glucose,lactate, corticosterone, live weight loss and the expression of heat shock protein 70 (T3 > T2 > T1, p<0.05). At d 0, the pre-rigor pH (pHi) and muscle glycogen were not significantly different among treatments but at days 1 and 7, the pH significantly increased (T3 > T2 > T1, p<0.05) while glycogen significantly reduced (T3 < T2 < T1, p<0.05) with transit time. Transportation reduced lightness (L*) of the meat (T3 < T2 < T1, p<0.05) but increased the redness (a*) (T3 > T2 > T1, p<0.05). Shear force values and drip loss were not influenced by transport duration (p>0.05) but cooking loss reduced with transport time (T1 > T2 > T3,p<0.05). No significant correlation was found between stress and meat quality parameters and despite their fluctuation, all stress parameters fell within the normal physiological range for rabbits. The second experiment aimed at determining physiological stress responses, meat quality, bleeding efficiency and storage stability upon subjecting rabbits to halal slaughter without stunning (HS) and gas stun killing (GK). Eighty male New Zealand White rabbits were divided into two groups of 40 animals and subjected to either HS or GK using 61.4% CO2, 20.3% oxygen and 18.3 % nitrogen. Both HS and GK caused a substantial increase in enzyme activities and the concentration of adrenaline, noradrenaline, glucose, lactic acid, calcium and white blood cells. Notably, GK exhibited significantly higher activities of LDH, AST and CK enzymes and the concentrations of adrenaline, noradrenaline and glucose. At d 0 and d 1, the glycogen content of GK and HS was not significantly different. However, at d 7, HS presented significantly greater glycogen than GK. At d 0, HS had significantly lower pHi than GK. However, at d 1 and d 7, the statistical significance was absent (p>0.05). At d 1, GK showed significantly greater lightness than HS. However, at d 7, the lightness of meat from both HS and GK did not significantly differ. Similarly, redness and enhanced redness of GK and HS did not significantly differ. At both d 1 and 7, the cooking loss for HS was significantly lower than that of GK. At d 1, HS exhibited significantly lower shear force values than GK although at d 7, the values for the two slaughter methods did not differ (p>0.05). The HS had presented significantly higher myofibril fragmentation index than the GK. Generally, slaughter caused an intense stress response. However, lack of correlation between stress parameters and meat quality characteristics indicates that the amount of stress might have been below the threshold to negatively affect rabbit meat quality. While their myoglobin content did not vary (p>0.05), HS resulted in significantly higher blood loss and lower residual haemoglobin than the GK. At 5 and 8 days of storage, GK exhibited significantly higher levels of malondialdehyde (lipid oxidation and bacterial counts than HS. Protein oxidation was not affected by slaughter method but increased with aging time through loss of thiols and the degradation of myosin heavy chain and troponin T. The study was further enriched with a proteomic approach to differentiate meat obtained by HS from that obtained by GK. Adenylate kinase, beta enolase, fructose ntly expressed thus suggesting their potential as biomarkers for slaughter and stunning methods pending validation and more studies. All in all, the present study has shown than that transport and slaughter caused substantial physiological stress responses, and even though these may not necessarily translate into compromising of animal welfare, care must be taken to avoid reaching the threshold to negatively affect meat quality. Additionally, the two slaughter methods did not influence protein oxidation but produced noticeable effects on lipid oxidation and microbial spoilage. Differential expression levels were detected in proteins of relevant metabolic and physiological roles.